Nowa PlaNETa: ku nadzorowanej wolności. Dyskursy i trendy - Krzysztofek, Kazimierz (Człowiek i Społeczeństwo, 2015)
The article is aimed at analyzing two trends, which at the same time constitute two discourses. The Author is focusing on their analysis avoiding to state to what extent they are contradictory or complementary, or in what degree they place themselves in different value orders, thus hardly subjected to be analyzed on a comparable scale. The first trend describes the dispersed, personalized and hyper-individualistic society whilst the second one is about a society heading for bureaucratization, quantification, monitoring and surveillance. Both trends are reflecting real processes of conflict and exchange. On the one hand they are gearing each other, and on the other hand they are in opposing relationships.